HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN PASSING ATAS SISWA EXTRAKULIKULER BOLA VOLI SMA NEGERI 12 PEKANBARU - Rezky Dayana Belasari Panjaitan; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:The purpose of this study is to determine the strenght of the arm and shoulder muscules to words overhand pass skill of voly ball.During the practice of passing on there were still many athletes who were less than optimal in overhand pass voly ball,so the results are not good. This research technique uses total sampling with a sample size of 12 students of the male volly ball extracuricular as SMA NEGERI 12 PEKANBARU. This research uses correlation technique. Then, the test data used the normality test, the moment correlation product test, α significant test α = 0,05. Normality test variable X, L0max (0,1300) < Ltabel (0,242), and variable normality test Y, L0max(0,1875) < Ltabel( 0,242) in other words the confidence level of 95% normal data and research conclusions indicate : a significant correlation between bisep power and overhand pass skill of voly ball extracurricular students, with a correlation r = 0,7067. Where r count > r tabel or 0,7067 > 0,602 and correlation are categorized as strong this, Ha is accepted.Key Words : Correlation, bisep power, overhand pass